Peran Vegetarisme dalam Membangun Kesejahteraan Spiritual Menurut Ajaran Buddha: Studi di Maha Vihara Maitreya Duta Palembang - Marshanda Rachma Mariska; Nugroho; Herwansyah (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2025)
This research aims to explore the role of vegetarianism in building spiritual well-being according to Buddhist teachings at Maha Vihara Maitreya Duta Palembang. This research uses a qualitative approach through interviews and literature studies with Buddhist practitioners and spiritual experts. The results and discussion of this study show that vegetarianism is in harmony with the core principles of Buddhism such as ahimsa (non-violence), Karuna (compassion), and metta (loving-kindness). This practice helps reduce negative karma and increase positive karma by avoiding killing animals for food consumption. Additionally, a vegetarian diet is also known to support the development of self-control, discipline and inner calm, which are essential in the Buddhist practice of meditation and contemplation. And it is recommended that future researchers be able to develop research like this even better so that it can fill in the deficiencies in this research.